Faktor-Faktor yang Memengaruhi Keputusan Pembelian pada produk Dessert di Wilayah Jakarta - Jannati Adeni Yuha; Usep Suhud; Rahmi Rahmi (VISA: Journal of Vision and Ideas, 2024)
The aim of this research is to examine the influence of viral marketing, price and product quality on perceptions. You can also test how purchase intentions influence purchasing decisions. This research was conducted using a survey method where questionnaires were distributed via Microsoft Forms in the Jakarta area. The population used in this research is consumers who have purchased Mixue products at least twice, live in Jakarta, and are aged 17 years and over. This research used a purposive sampling method with a total of 202 respondents. The approach used in this research is a quantitative approach using the SEM (Structural Equation Modeling) analysis method. The results of this research show that purchase intentions are positively and significantly influenced by viral marketing and product quality. Purchasing decisions are greatly influenced by purchasing intentions. Purchase intention is not significantly influenced by the price perception variable